2011
DOI: 10.52964/amja.0471
|View full text |Cite
|
Sign up to set email alerts
|

Acute Angle closure glaucoma (AACG): an important differential diagnosis for acute severe headache

Abstract: Acute headache is a common presenting symptom in the acute medical unit. We present a case of Acute Angle Closure Glaucoma (AACG) presenting with acute severe headache. It highlights the importance of remembering this ophthalmologic emergency and reminds us of its clinical presentation. The rapid assessment and diagnosis of AACG allowed prompt treatment and likely prevented the patient from losing her vision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…These different results can be due to the fact that in this study, the patient group also consisted of patients who had received therapy before coming to Dr. Mohammad Hoesin General Hospital, Palembang. [11][12][13][14] In terms of the therapy given, it was found that there were no findings at all with surgery/laser alone.…”
Section: Discussionmentioning
confidence: 99%
“…These different results can be due to the fact that in this study, the patient group also consisted of patients who had received therapy before coming to Dr. Mohammad Hoesin General Hospital, Palembang. [11][12][13][14] In terms of the therapy given, it was found that there were no findings at all with surgery/laser alone.…”
Section: Discussionmentioning
confidence: 99%